Novel solid electrolyte interface layer and manufacturing method thereof
By using liquid electrolytes compounded with lithium bisfluorooxalate borate and fluorovinyl carbonate, the liquid electrolyte cycling is carried out under a specific voltage window to form a new solid electrolyte interface layer rich in LiF, solving the problem of insufficient long cycle stability of WO3 electrodes and achieving efficient electrochromic performance and long life.
Patent Information
- Application Number
- CN202411207888.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2025-02-25
AI Technical Summary
In the prior art, WO3 electrodes have insufficient long cycle stability during electrochromic processes, conduction ion interpolation/detachment leads to structural changes and reduced optical modulation range, and unstable solid electrolyte interface layer causes side reactions and electrochemical degradation.
The liquid electrolyte obtained by combining lithium bisfluorooxalate borate with fluorovinyl carbonate or tris(2,2,2-trifluoroethyl)phosphate is circulated under a specific voltage window by cyclic voltammetry or multipotential step method to form a new solid electrolyte interface layer with a thickness of no less than 20 nm and rich in LiF.
The long cycle stability and electrochromic performance of WO3 electrodes are improved, the occurrence of side reactions is suppressed, the service life of the electrode is extended, and the irreversible capacity loss is reduced.
Smart Images

Figure CN119511593A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrolytes, and in particular to a novel solid electrolyte interface layer and a manufacturing method thereof. Background Art
[0002] In recent years, electrochromic devices have been widely used in smart windows, new energy vehicle canopies, sensors, new displays, flexible electronics, intelligent thermal control, military camouflage and other fields due to their unique stimulus response properties, outstanding advantages such as low power consumption, bistable state, and continuous stepless change. They play an important role in energy conservation and emission reduction and improving energy efficiency. At present, tungsten oxide (WO3) is one of the earliest discovered transition metal oxide cathode electrochromic materials. The electronic layer structure of metal ions is unstable. Under the condition of an external electric field, the ion valence state is easily changed, showing the coexistence of different valence states. Driven by a positive electric field, the conductive ions (including H + , Li + 、Na + 、Al 3+ When WO3 is intercalated with ions (such as ions, etc.) and undergoes an interfacial electrochemical reaction, it will cause WO3 to turn dark blue, which is called the colored state; under the drive of the reverse electric field, the conductive ions deintercalate WO3 and turn it into colorless and transparent, which is called the faded state. In the visible light region, the WO3 electrode achieves reversible color change; in the infrared region, the WO3 electrode achieves intelligent thermal regulation of the environment. Therefore, WO3 is considered to be one of the most promising cathode electrochromic materials.
[0003] At present, cathode electrochromic films such as WO3 usually encounter structural changes caused by the insertion / extraction of conductive ions during the electrochromic process, and the ions are easily trapped in the material, reducing the optical modulation range of the film, so its long-term cycle stability is easily degraded. For example, after 1000 cycles in H2SO4 electrolyte, the WO3 film prepared by inkjet printing showed an electrochromic degradation of up to 25% due to ion capture, showing unsatisfactory cycle stability, which seriously hindered its practical application. In addition, for LiClO4-PC electrolytes widely used in electrochromic devices, an unstable solid electrolyte interface (SEI) layer is usually formed at the electrode / electrolyte interface, which will cause a series of problems. First, the conductive ions (including H + , Li + 、Na + 、Al 3+ The repeated intercalation and deintercalation of the SEI layer leads to volume changes and more side reactions between the WO3 electrochromic electrode and the electrolyte. Secondly, the unstable SEI layer is constantly reassembled and thickened, resulting in an increase in the interface impedance. +The transmission rate is slowed down. Thirdly, the unstable SEI layer will produce uneven ion diffusion, which may cause degradation of electrochemical performance and structural collapse and lattice distortion of the electrode, making it difficult to obtain high-performance and high-stability WO3-based electrochromic devices. For example, the researchers used LiClO4-PC electrolyte, which showed a decrease in charge density and capacitance retention after cycling, and the electrode film fell off, which also limited the practical application of WO3 materials in electrochromic technology. Therefore, in order to improve the long-cycle stability and electrochromic performance of WO3 electrodes, the development of new electrolytes to form a solid electrolyte interface layer has become one of the key points of electrochromic technology products. Based on this, this patent invents a new electrolyte formula, proposes a low-cost and efficient method for forming a stable solid electrolyte interface layer, solves the problem of insufficient long-cycle stability of WO3 electrodes, and promotes the practical application of WO3-based electrochromic devices. Summary of the invention
[0004] In view of the above shortcomings of the prior art, the present invention provides a new solid electrolyte interface layer to solve the problems of instability of the solid electrolyte interface (SEI) layer formed by traditional electrolytes, increased interface impedance, and Li + The slow transmission rate, uneven ion diffusion and other deficiencies lead to technical problems such as degradation of electrochemical performance and collapse of electrode structure or lattice distortion. The present invention aims to improve the long cycle stability and electrochromic performance of cathode electrochromic electrode materials such as WO3, and promote the practical application of cathode electrochromic electrode materials such as WO3 in electrochromic devices.
[0005] In order to achieve the above purpose, the technical solution adopted by the present invention is:
[0006] A method for manufacturing a novel solid electrolyte interface layer, the method comprising the following steps:
[0007] S1: Weigh a certain amount of lithium perchlorate and lithium difluorooxalate borate according to a stoichiometric ratio, dissolve them in an organic solvent, and stir and mix them evenly to obtain a mixed solution;
[0008] S2: adding a certain amount of fluoroethylene carbonate or tris(2,2,2-trifluoroethyl)phosphoric acid to the mixed solution of step S1, and continuing to stir evenly to form a liquid electrolyte;
[0009] S3: using a conductive substrate as a substrate and depositing a cathode electrochromic material on the substrate;
[0010] S4: Using the liquid electrolyte formed in step S2 and the cathode electrochromic material obtained in step S3 as the working electrode, cyclic voltammetry or multi-potential step method is used. After cycling for not less than 10 cycles in a specific voltage window, a new solid electrolyte interface layer (SEI layer) with a thickness of not less than 20 nm and rich in LiF is in situ grown on the surface of the cathode electrochromic material.
[0011] The method for making a novel solid electrolyte interface (SEI) of the present invention is to obtain an optimized liquid electrolyte containing a composite additive by compounding lithium difluorooxalate borate with fluoroethylene carbonate or tri(2,2,2-trifluoroethyl)phosphoric acid. This electrolyte not only improves ion conductivity, but also enhances compatibility with electrode materials. Subsequently, a conductive substrate is used as a substrate to deposit a cathode electrochromic material, and cyclic voltammetry or multi-potential step method is used to cycle under a specific voltage window, which promotes the in-situ growth of a SEI layer of not less than 20nm thick and rich in LiF on the surface of the material. This LiF-rich SEI layer not only improves electrochemical stability and cycle stability, but also effectively passivates the electrode and inhibits the occurrence of side reactions due to its high electronic insulation and ionic conductivity. In addition, the thickness of the SEI layer of the present application and the proportion of LiF are precisely controlled, which ensures the optical modulation capability while providing sufficient protection and reducing irreversible capacity loss. These characteristics work together to greatly improve the performance and service life of electrochromic materials, and promote their commercial applications in the fields of smart windows and displays.
[0012] As a preferred technical solution, the organic solvent includes but is not limited to at least one high boiling point organic solution selected from the group consisting of propylene carbonate, ethylene carbonate, diethyl carbonate, dimethyl carbonate, N-methylpyrrolidone, butyl acetate, dimethyl sulfoxide, N,N-dimethylformamide, dimethylacetamide, γ-butyrolactone, and tetrahydrofuran.
[0013] As a preferred technical solution, the deposition method of the cathode electrochromic material includes but is not limited to at least one of electron beam evaporation, sol-gel method, magnetron sputtering method and electrochemical deposition method.
[0014] As a preferred technical solution, the cathode electrochromic material includes but is not limited to at least one of tungsten oxide, vanadium pentoxide, and niobium pentoxide.
[0015] As a preferred technical solution, the cyclic voltammetry method is performed in a voltage window of -1.5V to +1.5V at a scanning rate of 10 to 100mv / s.
[0016] As a preferred technical solution, the multi-potential step method is to perform periodic cycle operation under the operating conditions of voltages of -1V and 1V, and times of 10 to 60s and 10 to 60s, respectively.
[0017] As a preferred technical solution, the number of cycles of the cyclic operation is 10 to 40.
[0018] As a preferred technical solution, the thickness of the solid electrolyte interface layer is 20 to 50 nm.
[0019] As a preferred technical solution, the proportion of LiF in the solid electrolyte interface layer is 1-4%.
[0020] Another aspect of the present invention is to provide a novel solid electrolyte interface layer, which is manufactured by the manufacturing method of the novel solid electrolyte interface layer as described above.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The method for preparing a novel solid electrolyte interface layer of the present invention has the performance characteristics of good long-term cycle stability for the cathode electrochromic material electrode prepared. By introducing a two-component composite additive, on the one hand, the interface structure between cathode electrochromic materials such as WO3 and the electrolyte is improved, and a dense, thin, and LiF-rich SEI layer with protective characteristics is formed, which solves the problems of poor stability and low capacitance retention of the traditional electrolyte interface layer; on the other hand, the decomposition of the electrolyte during the charge and discharge process is reduced, the irreversible capacity loss is suppressed, and the long-term stability of the electrolyte is maintained. At the same time, the electrode material can be protected from electrolyte corrosion and the stress caused by ion intercalation / extraction can be relieved, thereby extending the service life of the electrode.
[0023] In general, the preparation method of the solid electrolyte interface layer of the present invention is simple and low-cost, and the obtained electrolyte interface layer enables the solid electrolyte in the electrochromic device to have excellent performance, thereby indirectly reducing the overall cost of the electrochromic device and improving production efficiency by improving the cycle efficiency and extending the service life of the electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a diagram of the action mechanism of the electrolyte additive in Example 1 of the present invention.
[0025] Figure 2 a is a transmission electron microscope (TEM) image of a cross section of the SEI layer of Example 1 of the present invention; Figure 2 b is the magnified TEM image of SEI / WO3 interface; Figure 2 c is a high-resolution transmission electron microscopy (HRTEM) image of a local cross section of the SEI layer; Figure 2 d is the HRTEM image of Li2CO3 and LiF nanocrystal particles.
[0026] Figure 3a and 3b are optical modulation retention diagrams of Example 1 of the present invention and Comparative Example 1, respectively. Figure 3 c is a graph showing the optical density versus charge density of Example 1 of the present invention and Comparative Example 1, Figure 3 d is the capacitance retention diagram of Example 1 of the present invention and Comparative Example 1.
[0027] Figure 4 a and 4b are high-resolution XPS spectrum depth profiles of the SEI layer of Example 1 of the present invention and Comparative Example 1, respectively; Figure 4 c and 4d are atomic composition ratio diagrams of the SEI layer of Example 1 of the present invention and Comparative Example 1 during XPS etching, respectively; Figure 4 e is a diagram showing the relative content of LiF in the SEI layer of Example 1 of the present invention.
[0028] Figure 5 a and 5c are the surface SEM images of comparative example 1 after 30 and 100 cycles, respectively; Figure 5 b and 5d are the surface SEM images of Example 1 of the present invention after 30 and 100 cycles, respectively.
[0029] Figure 6 a and 6c are the optical modulation retention diagram and the capacitance retention diagram of Comparative Example 2 of the present invention, Figure 6 b is the optical modulation retention diagram of comparative example 3 of the present invention. DETAILED DESCRIPTION
[0030] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations.
[0031] Example 1
[0032] The method for manufacturing the novel solid electrolyte interface layer of this embodiment comprises the following steps:
[0033] S1: 0.9 M lithium perchlorate (LiClO4) and 0.1 M lithium difluorooxalatoborate (LiDFOB) were weighed and dissolved in 100 ml of propylene carbonate (PC) according to the stoichiometric ratio, and the mixture was mixed uniformly under magnetic stirring for 30 min at room temperature to obtain a mixed solution;
[0034] S2: adding 2 wt % of fluoroethylene carbonate (FEC) to the mixed solution of step S1, and continuing to stir evenly to form a liquid electrolyte;
[0035] S3: Using conductive substrate ITO glass as a substrate, and depositing cathode electrochromic material tungsten oxide on the substrate; specifically, electron beam evaporation technology is used to prepare tungsten oxide thin film, and the deposition density is set to 7.16 mg / cm 2, substrate heating 200℃, deposition thickness 300nm, deposition rate
[0036] S4: Using the liquid electrolyte formed in step S2 and the cathode electrochromic material obtained in step S3 as the working electrode, cyclic voltammetry (CV) is performed at a voltage window of -1.5V to +1.5V at a scan rate of 50mv / s for 30 cycles. Then, a new solid electrolyte interface layer with a thickness of 37.18nm and rich in LiF (1%) is in situ grown on the surface of the tungsten oxide.
[0037] The formation of the novel solid electrolyte interface layer in this embodiment is mainly achieved by adding lithium difluorooxalatoborate (LiDFOB) in step S1 and fluoroethylene carbonate (FEC) in step S2 as additives to lithium perchlorate (LiClO4), and then cycling the electrolyte for 30 cycles under a specific voltage window. The mechanism of action of the additives in the electrolyte is as follows: Figure 1 As shown, specifically, the lowest unoccupied molecular orbital (LUMO) energy level and the highest occupied molecular orbital (HOMO) energy level of PC, FEC and LiDFOB calculated by density functional theory (DFT) show that the LUMO energy values of the two additives FEC and LiDFOB (0.52eV for FEC and -1.90eV for LiDFOB) are much lower than those of the PC solvent (1.00eV). Molecular orbital theory shows that molecules with lower LUMO energy have better acceptor properties and higher reactivity on negatively charged electrode surfaces. Therefore, during the initial cycle, LiDFOB will preferentially undergo reduction reaction to form a SEI layer containing LiF nanoparticles. The subsequent decomposition of FEC further increases the content of LiF. LiF has a high elastic modulus (about 65GPa), low Li + The diffusion barrier (0.19 eV in vacuum) and excellent electronic insulation can isolate electrons at the SEI / WO3 interface, effectively passivating the reaction surface to reduce initial side reactions, thereby inhibiting the continued decomposition of PC solvents. In addition, the LiF-rich SEI has high mechanical strength, which helps to better control Li + The volume change during the intercalation / extraction process reduces the risk of SEI deformation and rupture. Therefore, the electrolyte containing FEC and LiDFOB additives can form a thin, dense, and robust SEI, which can endow the WO3 electrode with stable cycling performance.
[0038] The SEI layer formed in Example 1 was analyzed by transmission electron microscopy (TEM). The results are as follows: Figure 2 Specifically, Figure 2Figures 2a and 2b show the nanostructure images observed using a high-resolution transmission electron microscope (HRTEM) after slicing the SEI layer formed using the novel solid electrolyte of this embodiment using the focused ion beam (FIB) processing technology. It can be seen that the SEI layer is uniformly and densely covered on the WO3 surface with a thickness of about 37.18 nanometers, further confirming the existence and uniformity of the SEI layer. High-resolution TEM image ( Figure 2 c) shows that the SEI layer contains a large number of nanocrystalline particles (about 3 nm in diameter) randomly dispersed in the amorphous matrix that wraps the WO3 electrode. These crystalline particles are the inorganic components of the SEI layer and can be determined as LiF and Li2CO3 by matching their lattice spacing. Generally, two groups of lattices with lattice spacings of 0.232 and 0.201 nm can be attributed to the LiF (111) and (200) lattice planes, respectively. In addition, other lattices with plane spacings of 0.208 and 0.225 nm also correspond to the Li2CO3 (-220) and (310) lattice planes, respectively ( Figure 2 d). The amorphous matrix may be an organic polymer formed by the decomposition of carbonate electrolyte. This result further confirms the successful introduction of LiF in SEI.
[0039] Comparative Example 1
[0040] The raw materials and preparation method of the solid electrolyte interface layer in this comparative example are basically the same as those in Example 1, except that, in the preparation method of this comparative example, a traditional electrolyte 1M LiClO4-PC (1M lithium perchlorate (LiClO4) is weighed according to a stoichiometric ratio and dissolved in 100ml of propylene carbonate (PC), and magnetically stirred for 30min at room temperature to mix evenly to obtain a mixed solution) is used instead of the liquid electrolyte prepared in step S2 of Example 1.
[0041] The electrochromic performance of Example 1 and Comparative Example 1 was tested in a three-electrode system with a Pt sheet as the counter electrode and Ag / AgCl as the reference electrode. The results are as follows: Figure 3 As shown; among them, Figure 3 a is a graph showing the optical modulation retention of a WO3 film (a solid electrolyte interface layer with a thickness of 37.18 nm and rich in LiF (1%) is in situ grown on its surface) using a novel electrolyte at 633 nm during 1500 continuous cycles in Example 1; Figure 3 b is a graph showing the optical modulation retention of the WO3 film using the conventional electrolyte in Comparative Example 1 during 1500 continuous cycles at 633 nm; Figure 3 c is a graph showing the variation of optical density of WO3 thin films using two different electrolytes, Example 1 and Comparative Example 1, with charge density at a wavelength of 633 nm; Figure 3 d is the current density of 1.74 mA / cm2 The capacitance retention of WO3 thin films with two different electrolytes, Example 1 and Comparative Example 1, is shown in FIG. Figure 3 It can be seen that the WO3 electrode using the novel solid electrolyte containing the additives of Example 1 (LiDFOB and FEC) exhibits excellent cycle stability. After 1500 cycles (90000s), the optical modulation range is still 82.8%, and the optical modulation retention rate is 90.87%, which is much higher than 44.18% and 53.92% in the traditional electrolyte ( Figure 3 b) By Figure 3 c It can be seen from the slope of the straight line area that the coloring efficiency of the new electrolyte is 55.29 cm 2 ·C -1 , which is also larger than the value measured in the traditional electrolyte (47.98 cm 2 ·C -1 ). Figure 3 d depicts the -2 The capacitance retention image obtained by constant current charge and discharge test at a current density of 2.5 ...
[0042] Furthermore, Example 1 and Comparative Example 1 were subjected to high-resolution XPS spectral analysis, atomic composition ratio analysis during XPS etching, and relative content test of LiF. The results are as follows: Figure 4 Specifically, from Figure 4 As can be seen in a and 4b, the C1s spectra of the WO3 electrode surface after cycling in the two electrolytes show three different CC, CO and OC=O groups at 284.8, 286.5 and 289.7 eV, respectively. These peaks correspond to alkane components, alkyl lithium carbonate (ROCO2Li) and Li2CO3, which are typical products of the SEI layer formed by the decomposition of carbonate solvents, indicating that the SEI layer is formed in both electrolytes. It is worth noting that the intensity of the CO peak in the C1s spectrum of the traditional electrolyte is higher ( Figure 4 b), indicating that the content of organic component ROCO2Li in its SEI layer is higher. Figure 4In a, the F 1s spectrum shows two peaks at 684.9 and 686.8 eV, corresponding to LiF and LiDFOB, respectively, confirming the successful introduction of LiF. LiF has excellent electronic insulation and high mechanical strength and is an ideal product of SEI. Figure 4 c and 4d depict the relative atomic concentrations calculated from the corresponding XPS spectra, indicating that the carbon ratio on the surface of the WO3 film after cycling in the novel electrolyte containing additives in Example 1 is lower than that in the conventional electrolyte, indicating that the introduction of the additives effectively inhibits solvent decomposition. In addition, the intensity of W detected using the conventional electrolyte is always relatively low throughout the etching process, indicating the presence of a thicker SEI layer. Figure 4 e shows the relative content of LiF calculated based on the relative atomic concentration of F and the F1s spectrum. It can be seen that LiF is distributed in the depth direction throughout the SEI layer, with a content ranging from 1 to 4%.
[0043] Furthermore, the surface SEM analysis test of Example 1 and Comparative Example 1 was performed, and the results are as follows: Figure 5 Specifically, Figure 5 The surface scanning electron microscope images of WO3 electrode after 30 and 100 cycles in the traditional electrolyte and the new electrolyte containing additives are shown. It can be seen that in the early stage of the cycle, the surface morphology of WO3 in both electrolytes is relatively smooth without obvious pores. It is worth noting that when the number of cycles reaches 100, obvious pores and cracks appear on the surface of SEI formed in the traditional electrolyte ( Figure 5 c) This structure indicates that corrosive parasitic reactions occur at the WO3 / electrolyte interface, and the electrolyte continues to decompose at low electrode potentials, indicating that the SEI layer cannot effectively prevent the occurrence of side reactions. In addition, the mechanical strength of the SEI layer formed in traditional electrolytes is not enough to withstand the Li + The continuous intercalation / extraction generates tensile and compressive stresses. Therefore, the SEI layer inevitably breaks, causing the WO3 surface to be exposed to the electrolyte again, triggering the regeneration and subsequent thickening of the SEI layer. This ultimately causes irreversible capacity loss and a decrease in the electrochromic performance of the WO3 film. In contrast, in the new electrolyte containing the additive, after 100 cycles, the SEI layer showed a denser and smoother appearance without any cracks or porous structures ( Figure 5 d) This difference can be attributed to the introduction of additives that promotes the formation of a strong LiF-rich SEI layer, which effectively passivates the electrode, inhibits the occurrence of side reactions, and has the ability to resist the influence of volume changes due to its excellent electronic insulation ability and high mechanical strength.
[0044] Comparative Example 2
[0045] The raw materials and the manufacturing method of the solid electrolyte interface layer in this comparative example are basically the same as those in Example 1, except that in the manufacturing method of this comparative example, the liquid electrolyte only contains the additive LiDFOB in step S1, and does not contain the additive FEC in step S2.
[0046] Comparative Example 3
[0047] The raw materials and the manufacturing method of the solid electrolyte interface layer in this comparative example are basically the same as those in Example 1, except that in the manufacturing method of this comparative example, the liquid electrolyte only contains the additive FEC in step S2, and does not contain the additive LiDFOB in step S1.
[0048] Comparative Examples 2 and 3 were tested for optical modulation and capacitance retention performance. The test results are as follows: Figure 6 As shown, Figure 6 a shows the optical modulation retention of WO3 film using electrolyte containing only LiDFOB additive during 1500 continuous cycles at 633nm; Figure 6 b shows the optical modulation retention of WO3 film using electrolyte containing only FEC additive during 1500 continuous cycles at 633 nm; Figure 6 c is the current density of 1.74 mA cm -2 The capacitance retention of WO3 thin film when using electrolyte containing only LiDFOB additive. Specifically, Figure 6 The different effects of the two additives are shown. Figure 6 a and 6b, it can be seen that the additive LiDFOB can effectively improve the optical cycle stability, while FEC has no obvious improvement effect. Figure 6 c and Figure 3 d, FEC plays a key role in improving capacitance retention. Therefore, the excellent performance of the electrode given by the SEI layer must rely on the synergistic effect of the two additives in the electrolyte.
[0049] It can be seen that the patent of the present invention has considerable advantages over the currently used technology. The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions only describe the principles of the present invention. The present invention may have various changes and improvements without departing from the spirit and scope of the present invention, and these changes and improvements fall within the scope of the present invention to be protected.
Claims
1. A method for preparing a novel solid electrolyte interface layer, characterized in that: The production method comprises the following steps: S1: Weigh a certain amount of lithium perchlorate and lithium difluorooxalate borate according to a stoichiometric ratio, dissolve them in an organic solvent, and stir and mix them evenly to obtain a mixed solution; S2: adding a certain amount of fluoroethylene carbonate or tris(2,2,2-trifluoroethyl)phosphoric acid to the mixed solution of step S1, and continuing to stir evenly to form a liquid electrolyte; S3: using a conductive substrate as a substrate and depositing a cathode electrochromic material on the substrate; S4: Using the liquid electrolyte formed in step S2 and the cathode electrochromic material obtained in step S3 as the working electrode, cyclic voltammetry or multi-potential step method is used. After cycling for not less than 10 cycles in a specific voltage window, a new solid electrolyte interface layer with a thickness of not less than 20 nm and rich in LiF is in situ grown on the surface of the cathode electrochromic material.
2. The method for preparing the novel solid electrolyte interface layer according to claim 1, characterized in that: The organic solvent includes, but is not limited to, at least one high boiling point organic solution selected from the group consisting of propylene carbonate, ethylene carbonate, diethyl carbonate, dimethyl carbonate, N-methylpyrrolidone, butyl acetate, dimethyl sulfoxide, N,N-dimethylformamide, dimethylacetamide, γ-butyrolactone, and tetrahydrofuran.
3. The method for preparing the novel solid electrolyte interface layer according to claim 1, characterized in that: The deposition method of the cathode electrochromic material includes but is not limited to at least one of electron beam evaporation, sol-gel method, magnetron sputtering method and electrochemical deposition method.
4. The method for preparing the novel solid electrolyte interface layer according to claim 1, characterized in that: The cathode electrochromic material includes but is not limited to at least one of tungsten oxide, vanadium pentoxide, and niobium pentoxide.
5. The method for preparing the novel solid electrolyte interface layer according to claim 1, characterized in that: The cyclic voltammetry method is performed in a voltage window from -1.5V to +1.5V at a scanning rate of 10-100mv / s.
6. The method for preparing the novel solid electrolyte interface layer according to claim 1, characterized in that: The multi-potential step method is to perform periodic cycle work under the operating conditions of voltages of -1V and 1V, and time of 10 to 60s and 10 to 60s, respectively.
7. The method for preparing the novel solid electrolyte interface layer according to claim 1, characterized in that: The number of turns of the cyclic operation is 10 to 40 turns.
8. The method for preparing the novel solid electrolyte interface layer according to claim 1, characterized in that: The thickness of the solid electrolyte interface layer is 20-50 nm.
9. The method for preparing the novel solid electrolyte interface layer according to claim 1, characterized in that: The LiF accounts for 1-4% of the solid electrolyte interface layer.
10. A novel solid electrolyte interface layer, characterized in that: The solid electrolyte interface layer is manufactured by the manufacturing method of the novel solid electrolyte interface layer according to any one of claims 1 to 9.